Students' perceptions of paper-based vs. computer-based testing in an introductory programming course - Barros, João Paulo (2019)
This paper examines the preferences of students regarding computer-based versus paper-based assessment, in an introductory computer programming course. Two groups of students were surveyed about their preference between paper-based and computer-based tests and respective rationale. All students had already been assessed: one group using two paper-based tests and the other group using two computer-based tests. Both groups expressed an overwhelming preference for computer-based tests independently of their previous programming experience. We conclude that, from the students' point of view, computer-based tests should be the used over paper-based ones for introductory programming courses. This adds to existing literature about computer-based testing of programming skills.